A Dynamic Model of Trade Union Contract Duration - Philip M. Bodman; Michael B. Devereux (Queen's University, Department of Economics, 1993)
There has been a great deal of research on trade unions and wage contracts in recent year, but there has been relatively little work on the determinants of contract length. This is unusual given that the duration of union contracts has varied substantially in post-war industrial economies both across time and across countries(see Dunlop J. and Bok D. (1970), Christofides L. N. and Wilton D. A. (1983), Ehrenberg Danziger and San (1984), Christofides L. N. (1985), Cecchetti (1987) and Bils M. (1987). This paper reviews the existing literature on contract duration and presents a simple explanation of optimal contract length for a wage setting trade union in a dynamic, uncertain environment. It is argued that optimal contract duration depends on a basic welfare trade-off between the benefits of wage precommitment and the costs of reduced ex-post wage flexibility. The cyclical characteristics of contracts in the model arguably provide an explanation for actual contractual cycles quite different from some alternative current models. The model may also be used to provide certain prediction concerning the determinants of contract length.
Keywords: J40; J41; J51; 330; dynamic; uncertain; trade union; wage contract; welfare trade-off; precommitment; ex-post flexibility; contractual cycles